PENGEMBANGAN PENUNTUN PRAKTIKUM MIKROBIOLOGI BERBASIS KETERAMPILAN PROSES SAINS MAHASISWA PENDIDIKAN BIOLOGI UIN ALAUDDIN MAKASSAR - Moh Mulyadi Prasetyo (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2016)
This research is a kind of research and development that is oriented to the development of quality education. The purpose of this study was to develop a device handbook microbiology lab-based science process skills are valid, practical and effective. This research was conducted at the Laboratory of Biology, Faculty of Tarbiyah and Teacher training UIN Alauddin Makassar. The subjects in this study were student class of 2011 Biology 4 semester of academic year 2013/2014. This procedure refers to the development of the model developed by Reiser and Mollenda is ADDIE (analysis, design, development, implementation and evaluation). Validity of the data obtained from the validation process by the experts. Validation of the results obtained some suggestions and made revisions to produce a valid prototype 1. Practicality of data obtained through adherence to the guiding instrument lab observation sheet while the effectiveness of the data obtained through observation of the activity sheet instruments, lab test results and questionnaire responses. The results of the field test showed that the guidebook Microsbiology Lab work based skill the process of science have met the criteria indicator practicality with all aspects including syntax aspects, social interaction and reaction principles are implemented entirely in the category. Effectiveness criteria are also met with indicator (i) the activity of the practitioner in the category largely accomplished. (ii) achieve mastery test lab results with the percentage of 91.11% and an average value of 60.41. (iii) the practitioner's response is in the positive category. Based on expert evaluations and test results show that the guiding practice science process skills-based Microbiology meeting the criteria of validity, practicality and effectiveness.